2005
DOI: 10.1111/j.1365-2699.2005.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Chilean coastal forests pre‐Pleistocene relicts? Evidence from foliar physiognomy, palaeoclimate, and phytogeography

Abstract: Aim We ask whether contemporary forests of the Chilean Coastal Range can be considered to be direct and conservative descendants of pre-Pleistocene palaeofloras that occurred in southern South America from the Palaeogene to early Neogene periods (65-10 Ma), maintaining foliar physiognomies that do not match their present-day climate. We also identify the most likely ancestors of present-day coastal forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 20 publications
1
54
0
2
Order By: Relevance
“…These plants may have persisted because of the oceanic climate which allowed, in that area, the existence of a refuge (Villagrán et al 1998). Hinojosa et al (2006) reported that the mixed palaeoflora, which developed in Central Chile during the Oligocene to Miocene transition (ca. 25 million years ago), is closely related to the remnant deciduous Maulino forest.…”
Section: Systematicsmentioning
confidence: 99%
“…These plants may have persisted because of the oceanic climate which allowed, in that area, the existence of a refuge (Villagrán et al 1998). Hinojosa et al (2006) reported that the mixed palaeoflora, which developed in Central Chile during the Oligocene to Miocene transition (ca. 25 million years ago), is closely related to the remnant deciduous Maulino forest.…”
Section: Systematicsmentioning
confidence: 99%
“…A second fossil flora was described at Boca Pupuya, biostratigraphically dated to the transition from Early to Middle Miocene (Troncoso, 1991;Troncoso and Romero, 1993;Encinas, 2006). It comprises lower number of Nothofagus morphotaxa and higher subtropical elements (particularly, Neotropical Myrtaceae and Pantropical Lauraceae) compared to Mixed Paleofloras, and thus it was classified as Neogene Subtropical Hinojosa et al, 2006). Using the same leaf physiognomic analysis mentioned above, the estimated mean annual temperature was 21.4°C and the annual precipitation 931 mm (Hinojosa and Villagrán, 2005).…”
Section: Geological and Palaeontological Settingmentioning
confidence: 99%
“…En resumen, los resultados alcanzados d e s d e e l p u n t o d e v i s t a p a l i n o l ó g i c o confi rmarían la presencia de Paleofl oras Mixtas para el Mioceno de Chile central, originalmente propuesta por Troncoso (1991), y también los modelos paleovegetacionales planteados para el Neogeno de Chile central (Hinojosa 2005, Hinojosa et al 2006; se destaca el primer registro de taxones endémicos de las familias Calyceraceae y -Barnadesioideae-Asteraceae para la palinofl ora del país.…”
Section: Tipos De Vegetación Y Paleoclimaunclassified
“…Así, los modelos paleofitogeográficos muestran la sucesión temporal y espacial de diferentes unidades paleoflorísticas, desde Tropicales-Subtropical G o n d w á n i c a s a M i x t a s y S u b t r o p i c a l Neógenas, estas últimas desarrollándose preferentemente en las áreas centrales de Chile y Argentina (Hinojosa 2005, Hinojosa et al 2006). La sucesión de estas floras se encuentra íntimamente ligada a al menos tres escenarios climáticos contrastantes que caracterizan estos tiempos: (1) condiciones tropicales-subtropicales, cálidas y húmedas relacionadas a un óptimo climático global durante fi nes del Paleoceno a principios del Eoceno; (2) condiciones más templadas y más secas hacia el fi nal del Eoceno y principios del Oligoceno, relacionado con el evento de enfriamiento global del límite Eoceno/ Oligoceno (consecuencia de la glaciación Antártica); (3) fi nalmente, durante el Mioceno un nuevo evento cálido húmedo, durante el cual la temperatura media anual aumentó entre 6° y 9° C comparado con el período anterior (Hinojosa & Villagrán 1997, 2005, Hinojosa 2005, Hinojosa et al 2006. Para Chile central el aporte de restos vegetales referidos al Neógeno provienen preferentemente de la Formación Navidad, los cuales han sido claves para el entendimiento de la evolución fl orística del área, en especial a lo referente al estudio de macrorrestos (hojas fósiles), sin embargo los modelos paleofitogeográficos como el descripto más arriba no han sido sometidos a refutación con evidencia palinológica.…”
unclassified